2014
DOI: 10.1182/blood.v124.21.796.796
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Outcomes for Older Adolescents and Young Adults (AYA) with Acute Lymphoblastic Leukemia (ALL): Early Results of U.S. Intergroup Trial C10403

Abstract: Background: Retrospective analyses have demonstrated significantly improved survival for AYA ALL patients (pts) aged 16-21 years (yrs) when treated on pediatric versus adult U.S. NCI Cooperative group regimens where 2-yr event-free survivals (EFS) have been only 35-40%. The purpose of C10403, a large prospective US intergroup trial, was to evaluate the feasibility and effectiveness [with EFS as a primary endpoint), of treating AYA ALL pts (ages 16-39 yrs) using the standard arm of the successful Children's Onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 0 publications
1
58
1
Order By: Relevance
“…19,20 The year of diagnosis was categorized as 2004 to 2007, 2008 to 2012, and 2013 to 2014, reflecting potentially relevant events in AYA ALL, including the accrual period of the US Adult Intergroup Study C10403 from 2008 through 2012. 14 We reviewed all available GBACR facility-level reports for each patient. These facility-level reports reflect information reported to the GBACR from each facility, and normally are consolidated to the tumor level when reported to SEER.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 The year of diagnosis was categorized as 2004 to 2007, 2008 to 2012, and 2013 to 2014, reflecting potentially relevant events in AYA ALL, including the accrual period of the US Adult Intergroup Study C10403 from 2008 through 2012. 14 We reviewed all available GBACR facility-level reports for each patient. These facility-level reports reflect information reported to the GBACR from each facility, and normally are consolidated to the tumor level when reported to SEER.…”
Section: Methodsmentioning
confidence: 99%
“…14 Among 318 AYA patients aged 17 to 39 years who were enrolled from 2007 through 2012, the 2-year event-free survival and overall survival rates were 66% and 78%, respectively, which was considerably higher than the event-free survival and overall survival rates of 34% and 46%, respectively, of historical controls treated on US adult cooperative group trials for ALL. 14 With accumulating evidence supporting the theory that AYA patients with ALL should be treated according to pediatric-inspired protocols, many potential obstacles exist in the United States. Although ALL is the most commonly occurring malignancy in children, it occurs less frequently in adults, accounting for only 15% of all adult leukemia and 0.4% of adult cancer diagnoses in the United States.…”
Section: Introductionmentioning
confidence: 91%
“…Although new treatment approaches for AYA ALL are being used, the results from these studies are just now becoming available and are not reflected in these survival data. 6 These data underscore the importance of continuing to monitor trends over time of specific cancers to guide future research efforts. Workshop participants agreed that there is a need to develop research resources and platforms to continue such surveillance.…”
Section: Epidemiologymentioning
confidence: 99%
“…Having met its target accrual of 300 patients ages 16 to 39 years, C10403 represents a landmark effort in scientific collaboration among the participating NCI cooperative oncology groups and a significant step in increasing access to optimal ALL therapy for the full breadth of the AYA population. 6 The CTSU is a service NCI provides to facilitate access to cancer treatment trials across the United State and Canada. COG studies relevant to AYAs are posted on the CTSU Website, making it easier for medical oncologists to enroll eligible patients on these trials.…”
Section: Barriers To Enrollment and Strategies To Overcome Themmentioning
confidence: 99%
“…A recent study demonstrated that MRD positivity on day 28 following induction chemotherapy is associated with an adverse outcome. 14 MRDpositive patients are generally recommended for HSCT at the first complete remission. 15…”
mentioning
confidence: 99%